2006
DOI: 10.1152/ajpendo.00283.2005
|View full text |Cite
|
Sign up to set email alerts
|

Acute, same-day effects of antecedent exercise on counterregulatory responses to subsequent hypoglycemia in type 1 diabetes mellitus

Abstract: . Acute, sameday effects of antecedent exercise on counterregulatory responses to subsequent hypoglycemia in type 1 diabetes mellitus. Am J Physiol Endocrinol Metab 290: E1331-E1338, 2006. First published January 31, 2006 doi:10.1152/ajpendo.00283.2005.-Exercise-induced hypoglycemia can occur within hours after exercise in type 1 diabetes mellitus (T1DM) patients. This study tested the hypothesis that an acute exercise bout causes (within hours) blunted autonomic and metabolic responses to subsequent hypoglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
48
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 37 publications
(29 reference statements)
1
48
3
Order By: Relevance
“…DagogoJack et al (32) demonstrated that hypoglycemic symptoms can increase before adrenomedullary or sympathetic neural responses in patients with hypoglycemia-associated autonomic failure (32). Sandoval et al (33) and Davis et al (17) also demonstrated that hypoglycemic symptoms are preserved relative to blunting of other ANS responses following antecedent stress. Thus, previous studies seem to indicate that hypoglycemic symptoms are resultant of central ANS drive and are preserved high in the hierarchy of ANS responses to hypoglycemia.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…DagogoJack et al (32) demonstrated that hypoglycemic symptoms can increase before adrenomedullary or sympathetic neural responses in patients with hypoglycemia-associated autonomic failure (32). Sandoval et al (33) and Davis et al (17) also demonstrated that hypoglycemic symptoms are preserved relative to blunting of other ANS responses following antecedent stress. Thus, previous studies seem to indicate that hypoglycemic symptoms are resultant of central ANS drive and are preserved high in the hierarchy of ANS responses to hypoglycemia.…”
Section: Discussionmentioning
confidence: 95%
“…The origin of hypoglycemic symptoms during hypoglycemia is complex. Previous studies demonstrated scenarios whereby discordant responses between autonomic symptoms and catecholamine responses can exist during hypoglycemia (17,(31)(32)(33). Generally, studies have determined that autonomic symptoms can be preserved despite reduced activity in other branches of the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Its lower concentrations in the afternoon and particularly at midnight may favor hypoglycemia by reducing gluconeogenesis and responses to glucagon. 7,8 Further research is needed to better quantify this phenomenon. Other possible explanation could be the absence of insulin boluses before the morning exercise since these was performed in a fasting state, however, we aimed to reduce this difference as the afternoon exercise session was conducted 4 hours after lunch, which is considered enough time to minimize the effect of the fast-acting insulin used for that meal.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycemia-associated autonomic failure following prior exercise or hypoglycemia is only experienced with peripheral insulin delivery in T1D. 23,41,57,[69][70][71][72][73][74][75] What Should Future Technology Offer to Best Manage Diabetes With Exercise?…”
mentioning
confidence: 99%